Children's future parasocial relationships with media characters: the age of intelligent characters. Issue 2 (2nd April 2016) - Brunick, Kaitlin L.; Putnam, Marisa M.; McGarry, Lauren E.; Richards, Melissa N.; Calvert, Sandra L.
Abstract: Children experience emotionally tinged parasocial relationships with their favorite media characters across a constantly changing media landscape. On the frontier of this landscape are intelligent agents: digital companions that can socially interact with and educate children. We discuss how research on parasocial relationships with media characters can influence the design of intelligent "characters" for children. We discuss the components of parasocial relationships—including attachment, character personification, and social realism—and how these may play a role in developing intelligent characters as effective educational tools. We also examine the development and dissolution of parasocial relationships, and how these factors can inform intelligent character design. Educational and social implications for these technologies as teaching tools are also discussed.